Asymmetrical subcortical plasticity entails cognitive progression in older individuals. Issue 1 (21st December 2018) - Esteves, Madalena; Moreira, Pedro S.; Marques, Paulo; Castanho, Teresa C.; Magalhães, Ricardo; Amorim, Liliana; Portugal‐Nunes, Carlos; Soares, José M.; Coelho, Ana; Almeida, Armando; Santos, Nadine C.; Sousa, Nuno; et al.
Abstract: Structural brain asymmetries have been associated with cognition. However, it is not known to what extent neuropsychological parameters and structural laterality covary with aging. Seventy‐five subjects drawn from a larger normal aging cohort were evaluated in terms of MRI and neuropsychological parameters at two moments (M1 and M2), 18 months apart. In this time frame, asymmetry as measured by structural laterality index (ΔLI) was stable regarding both direction and magnitude in all areas. However, a significantly higher dispersion for this variation was observed in subcortical over cortical areas. Subjects with extreme increase in rightward lateralization of the caudate revealed increased M1 to M2 Stroop interference scores, but also a worsening of general cognition (MMSE). In contrast, subjects showing extreme increase in leftward lateralization of the thalamus presented higher increase in Stroop interference scores. In conclusion, while a decline in cognitive function was observed in the entire sample, regional brain asymmetries were relatively stable. Neuropsychological trajectories were associated with laterality changes in subcortical regions.